Does Immunohistochemistry Represent a Robust Alternative Technique in Determining Drugable Predictive Gene Alterations in Non-Small Cell Lung Cancer? - Rossi, Giulio; Ragazzi, Moira; Tamagnini, Ione; C. Mengoli, Maria; Vincenzi, Giada; Barbieri, Fausto; Piccioli, Silvia; Bisagni, Alessandra; Vavala, Tiziana; Righi, Luisella; Novello, Silvia; Gelsomino, Francesco; et al. (Current Drug Targets, 2017)
Immunohistochemistry (IHC) is a widely-tested, low-cost and rapid ancillary technique available in all laboratories of pathology. This method is generally used for diagnostic purposes, but several studies have investigated the sensitivity and specificity of different immunohistochemical antibodies as a surrogate test in the determination of predictive biomarkers in non-small cell lung cancer (NSCLC), particularly for Epidermal Growth Factor Receptor (EGFR) gene mutations, Anaplastic Lymphoma Kinase (ALK) gene and ROS1 rearrangements. In this review, a critical examination of the works comparing the consistency of IHC expression and conventional molecular techniques to identify genetic alterations with predictive value in NSCLC is discussed. Summarizing, data on sensitivity and specificity of antibodies against ALK and ROS1 are very consistent and time has come to trust in IHC at least as a cost-effective screening tool to identify patients with rearranged tumors in clinical practice. On the other hand, mutant-specific antibodies against EGFR demonstrate a good specificity but a lowto- fair sensitivity, raising some cautions on their employment as robust predictive biomarkers. A brief comment on preliminary experiences with antibodies against BRAF, RET, HER2 and c-MET is also included.
Keywords: EGFR